(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
The article offers a solution to the problem of production and segmentation in the market of care cosmetics both in Russia and in other countries. Rarely used in our country, the mechanism of added value, as well as the niche in the market of professional hair care products, show high prospects for the distribution of this cosmetics among domestic beauty salons and the potential entry of this segment into the foreign market.